The Legal Status of Non-Civil-Servant Employees Appointed by Rectors at State Universities with Legal Entity Status: Between the Labor Law and Civil State Apparatus Regimes - Shafira Hilda Tryana; Istislam Istislam; Herman Suryokumoro (International Journal of Business, Law, and Education, 2026)
This article examines the legal status of non-civil-servant employees appointed by rectors at Indonesian State Universities with Legal Entity Status (Perguruan Tinggi Negeri Badan Hukum, PTN-BH). The issue is legally significant because PTN-BH institutions are autonomous public legal entities that perform state functions in higher education while simultaneously exercising managerial authority comparable to that of employers in ordinary employment relationships. Using normative legal research with statutory, conceptual, and prescriptive approaches, this study analyses whether rector-appointed non-civil-servant employees should be governed by the Civil State Apparatus (Aparatur Sipil Negara, ASN) regime or by Indonesian labor law. The analysis shows that these employees fall outside the formal scope of Law Number 20 of 2023 on the Civil State Apparatus because the ASN regime recognizes only Civil Servants (PNS) and Government Employees under Employment Agreements (PPPK), both of whom are appointed through the national civil-service management system. By contrast, the relationship between PTN-BH and rector-appointed employees contains the cumulative elements of an employment relationship under Indonesian labor law: work, wages, and command or subordination. The article argues that the problem is not a direct conflict between two statutes, but a regulatory vacuum arising from the hybrid institutional position of PTN-BH. Pending the enactment of a specific statutory framework, labor law provides the most coherent legal basis for protecting these employees' rights, including remuneration, social security, termination protection, and industrial dispute settlement. The article recommends regulatory harmonization to clarify their legal status while preserving the institutional autonomy of PTN-BH.